Protocol for performing angiogenic and tumorigenic assays using the in ovo chick embryo chorioallantoic membrane model - Tommy Chastel; Serena Filiberti; Stefania Mitola; Roberto Ronca; Andrei Turtoi; Michela Corsini (STAR Protocols)
Summary: The chick embryo chorioallantoic membrane (CAM) is a viable alternative in vivo model to explore cancer biology due to its simplicity, accessibility, and cost-effectiveness. Here, we present a protocol for performing angiogenic and tumorigenic assays using the in ovo chick embryo CAM model. We describe steps for initial general preparation and for the angiogenic and tumorigenic assays in two distinct sections. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.